Implementation of the Integrated Justice System as an Effort to Prevent Sexual Violence against Children: A Case Study in Indonesia - Miftahul Jannah; Andi Sri Rezky Wulandari; Mekkah HM; Aat Ruchiat Nungraha; Diah Fatma Sjoraida (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
Sexual violence against children is a serious problem that threatens the safety and well-being of the younger generation. This study aims to analyze the implementation of the integrated justice system as an effort to prevent sexual violence against children in Indonesia. The integrated justice system integrates various institutions, including the police, prosecutor's office, courts, and child protection services, to ensure comprehensive protection for children as potential victims. This study uses a case study approach with a focus on policy implementation at the national and regional levels, as well as evaluating the effectiveness of collaboration between institutions in preventing sexual violence against children. The results show that although the integrated justice system has been well designed, there are still challenges in coordination between institutions, policy understanding at the local level, and limited resources that affect the effectiveness of prevention. The recommendations of this study include strengthening the capacity of related institutions, increasing coordination between institutions, and wider socialization about the importance of protecting children from sexual violence. Thus, it is hoped that the implementation of an integrated justice system can be an effective solution in preventing sexual violence against children in Indonesia.